2006
DOI: 10.1108/09547540610704774
|View full text |Cite
|
Sign up to set email alerts
|

Motivational factors of gender, income and age on selecting a bottle of wine

Abstract: Purpose -To explore the attributes of wine packaging that are enticing to consumers and the influence of age, gender and income on the wine-buying decision. Design/methodology/approach -To evaluate how wine packaging interplays with age, gender and income to influence consumers' decision to purchase. A self-administered questionnaire with closed-ended and five-point Likert-type scale questions was conducted in the State of Connecticut at two retail shops and five wineries. The questionnaire was pilot-tested at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
159
5
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(181 citation statements)
references
References 20 publications
13
159
5
4
Order By: Relevance
“…In contrast, females rely on a broad variety of information and they usually attempt an elaboration of all available information unless they are restricted by memory constraints. In the hotel and food industry, decisionmaking processes were shown to be more time consuming among females and high age groups, while income seems not to play an effect (Barber et al, 2006;Han et al, 2009). Based on the above arguments and on the evolutionary psychology literature on impulsiveness (Cross et al, 2011;Wilska, 2003), we argue that there is a demographic effect in the trade-off between using multiple pieces of information and saving time and cognitive effort.…”
Section: Reducing Uncertainty or Following The Crowdmentioning
confidence: 79%
“…In contrast, females rely on a broad variety of information and they usually attempt an elaboration of all available information unless they are restricted by memory constraints. In the hotel and food industry, decisionmaking processes were shown to be more time consuming among females and high age groups, while income seems not to play an effect (Barber et al, 2006;Han et al, 2009). Based on the above arguments and on the evolutionary psychology literature on impulsiveness (Cross et al, 2011;Wilska, 2003), we argue that there is a demographic effect in the trade-off between using multiple pieces of information and saving time and cognitive effort.…”
Section: Reducing Uncertainty or Following The Crowdmentioning
confidence: 79%
“…Previous studies have shown that involvement impacts the product attributes which consumers choose to evaluate a wine (Bruwer and Huang, 2012;Barber et al, 2008a;Quester and Smart, 1996;Zaichkowsky, 1985) and that it can be used to segment the wine market (Lockshin et al, 1997(Lockshin et al, , 2001). Moreover, international research has shown that demographic variables such as gender (Forbes, 2012;Barber et al, 2006) or age (Fountain and Lamb, 2011;Thomas and Pickering, 2005;Goldsmith and d'Hauteville, 1998) affect the wine purchase.…”
Section: Introductionmentioning
confidence: 99%
“…Green purchasing is essentially the act of buying environmental friendly products. The research model in this study examines the consequences of predictor variables (environmental concern, organizational green image and environmental knowledge) upon criterion variable (green purchase intention) with the moderating effect of perceived product price and quality Rettie & Brewer, 2000;Barber, Almanza, & Donovan, 2006). Adelina & Morgan (2007) conclude that Packaging could be treated as one of the most valuable tool in today's marketing communications; Packaging has an important impact on consumers buying behaviour.…”
Section: Background Of the Studymentioning
confidence: 99%